Lessons learned from the largest tenure mix operation in the world: Right to buy in the United Kingdom - Reinout Kleinhans; Maarten van Ham (Institute for the Study of Labor (IZA), 2013)
In the last few decades, urban renewal policies have taken firm root in many Western European countries. Underlying these renewal policies is a strong belief in negative neighborhood effects of living in poverty concentration areas, often neighborhoods with a large share of social housing. In Europe, great importance is attached to creating a more diverse housing stock (in terms of tenure and dwelling types) and as a means to establish a more socially mixed neighborhood population. Mixed housing strategies are stated explicitly by governments in the Netherlands, the United Kingdom, Germany, France, Finland and Sweden. The idea is that mixing homeowners with social renters will create a more diverse socio-economic mix in neighborhoods, removing the potential of negative neighborhood effects. By far the largest tenure mix operation in Europe is the Right to Buy (RTB) scheme in the United Kingdom. Since the 1970s, over 2.7 million social rented houses have been sold with large discounts, mainly to sitting tenants. In this paper we synthesize the outcomes of RTB with regard to neighborhood impacts: residualisation, neighborhood stability, tenure mix and social mix, social interactions, and dwelling maintenance. Although we acknowledge substantial socioeconomic benefits of the RTB for many individual residents, we find that the neighborhood outcomes of RTB are by no means solely beneficial.
Keywords: J61; R21; R23; R28; 330; Right to Buy; tenure mix; neighbourhood effects; urban renewal; residential mobility; poverty neighbourhoods